Jasmonic acid‐responsive AabHLH1 positively regulates artemisinin biosynthesis in Artemisia annua. (13th February 2019) - Li, Ling; Hao, Xiaolong; Liu, Hang; Wang, Wei; Fu, Xueqing; Ma, Yanan; Shen, Qian; Chen, Minghui; Tang, Kexuan
Abstract: Artemisia annua is the only natural source of the sesquiterpenoid artemisinin, which is widely used to treat malaria. The phytohormone jasmonic acid (JA) can significantly promote artemisinin biosynthesis in A. annua . AabHLH1 can bind and activate artemisinin biosynthetic genes, such as AaADS and AaCYP71AV1 . In this study, we proved that AabHLH1 was responsive to MeJA treatment and highly expressed in glandular trichome‐enriched tissues, and that its expression profile was similar to that of AaADS . Yeast two‐hybrid assays showed that AabHLH1 interacted with all nine AaJAZ proteins in A. annua . Functional analysis with transgenic plants showed that several artemisinin biosynthetic genes were upregulated in AabHLH1‐OE transgenic A. annua lines and downregulated in AabHLH1‐EAR lines; furthermore, the artemisinin content was increased in the AabHLH1‐OE lines and decreased in the AabHLH1‐EAR lines. These results demonstrate that the JA‐induced AabHLH1 positively regulates artemisinin biosynthesis by regulating the biosynthetic genes, and thus provide new insight into the regulatory mechanism of JA‐induced artemisinin biosynthesis in A. annua .